2021
DOI: 10.1007/s13410-021-00930-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics and outcomes of COVID-19 in diabetic versus non-diabetic patients

Abstract: Objectives and background People with diabetes (PWD) are one of the high-risk groups for coronavirus disease 2019 (COVID-19) infection, increasing the disease mortality. This study was aimed to compare the epidemiological characteristics and outcomes of COVID-19 in diabetic versus non-diabetic individuals. Methods In this retrospective observational study, the epidemiological characteristics of the two groups of diabetic ( n =1365) and non-dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 23 publications
2
13
1
Order By: Relevance
“…In support of our findings, diabetes has been widely suggested by previous studies as a mortality and poor outcome predictor among COVID-19 patients. [30][31][32] Moreover, mortality of COVID-19 patients with co-existing CVD was higher compared to the healthy ones, but we did not find a statistically significant difference. Similar to our findings, three studies conducted in Georgia, Brazil, and Italy, reported CVD patients to have a higher mortality rate, but they did not detect CVD as a significant mortality predictor.…”
Section: Discussioncontrasting
confidence: 68%
“…In support of our findings, diabetes has been widely suggested by previous studies as a mortality and poor outcome predictor among COVID-19 patients. [30][31][32] Moreover, mortality of COVID-19 patients with co-existing CVD was higher compared to the healthy ones, but we did not find a statistically significant difference. Similar to our findings, three studies conducted in Georgia, Brazil, and Italy, reported CVD patients to have a higher mortality rate, but they did not detect CVD as a significant mortality predictor.…”
Section: Discussioncontrasting
confidence: 68%
“…The prevalence of COVID-19 positive diabetics in hospitalized patients varies across the Middle East. it was 19.5% in Qatar [31], 29.3% in Kuwait [32], 8.3% in Iran [33] and 31.2% in UAE [34].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, more than three-fourths of the diabetic patients were hypertensive, 50% had CVD, and were significantly older than non-diabetic patients. These factors can increase the risk of poor disease prognosis [33][34][35]. COVID-19 is a multisystem infection rather than only a respiratory infection.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-four papers were reviewed after screening, which reported the incidence of hyperlipidemia in COVID-19 patients ( Table 2 ). 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 The incidence of hyperlipidemia ranged from 0.30% to 81.82% in COVID-19 patients among different studies. Potential reasons for the variations could be: 1) Regional factors led to the difference in baseline lipids levels; 2) The definition of hyperlipidemia varied in different studies.…”
Section: The Correlation Between Hyperlipidemia and Covid-19mentioning
confidence: 99%